2019
DOI: 10.1103/physrevd.99.115003
|View full text |Cite
|
Sign up to set email alerts
|

Minimal spin-one isotriplet dark matter

Abstract: In this work we present a simple extension of the Standard Model that contains, as the only new physics component, a massive spin-one matter field in the adjoint representation of SU (2) L . In order to be consistent with perturbative unitarity, the vector field must be odd under a Z 2 symmetry. Radiative corrections make the neutral component of the triplet (V 0 ) slightly lighter than the charged ones. We show that V 0 can be the dark matter particle while satisfying all current bounds if it has a mass betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 79 publications
1
27
0
Order By: Relevance
“…The scalar sector of the IDM contains 1 inert doublet, which is Z 2 -odd, does not develop a Vacuum Expectation Value (VEV) and does not couple to fermions, and 1 active Z 2 -even Higgs doublet, which has a non-zero VEV and couples to fermions in the same way as the SM Higgs doublet, hence also referred to as I(1+1)HDM. The IDM, however constrained, is a viable model that can provide a viable DM candidate (see the latest analyses, e.g., in [8,9,10,11]). However, due to the imposed exact Z 2 symmetry, all parameters in the potential are real and there is no room for additional sources of CP-violation.…”
Section: Introductionmentioning
confidence: 99%
“…The scalar sector of the IDM contains 1 inert doublet, which is Z 2 -odd, does not develop a Vacuum Expectation Value (VEV) and does not couple to fermions, and 1 active Z 2 -even Higgs doublet, which has a non-zero VEV and couples to fermions in the same way as the SM Higgs doublet, hence also referred to as I(1+1)HDM. The IDM, however constrained, is a viable model that can provide a viable DM candidate (see the latest analyses, e.g., in [8,9,10,11]). However, due to the imposed exact Z 2 symmetry, all parameters in the potential are real and there is no room for additional sources of CP-violation.…”
Section: Introductionmentioning
confidence: 99%
“…Production of D + in pairs or in association with DM leads then to the typical signature from charged LLP: disappearing charged track (DCT) as soon as the track from LLP is long enough (from few cm to a meter). In case of such signature the S/B ratio is much higher than in case of mono-jet signal and therefore, substantially bigger DM masses can be probed with charged LLPs from DM sector [34][35][36]. As an example, we would like to present here results for the minimal vector triplet DM (V 0 ) model [36] which predicts the right amount of DM for M DM in the 3-4 TeV range depending on DM coupling to the Higgs boson.…”
Section: Beyond Mono-x Signaturementioning
confidence: 94%
“…The mass split, M, between V 0 and V ± is generated radiatively and its value is just above the pion mass which makes V ± long lived. In Figure 6 we present M as a function of M V , which was calculated in Belyaev et al [36].…”
Section: Beyond Mono-x Signaturementioning
confidence: 97%
See 1 more Smart Citation
“…However, it has been shown that vector bosons may perfectly play the role of dark matter, most of them motivated from hidden gauge sectors [15][16][17][18][19][20][21][22][23][24], extra large dimensions [25], little Higgs model [26] and from a linear sigma model [27]. Recently, the neutral component of an electroweak vector multiplet has been shown to be a good dark matter candidate, such as multiplets transforming in the adjoint representation [28], and in the fundamental one in the context of 331 models [29,30] and in Gauge-Higgs unification framework [31].…”
Section: Introductionmentioning
confidence: 99%